Effect of acupressure on anxiety among cancer patients undergoing chemotherapy: A systematic review - Tara Alizadeh; Poorya Takasi (Journal of Nursing Reports in Clinical Practice)
This systematic review was conducted to investigate the impact of acupressure on anxiety levels among cancer patients undergoing chemotherapy. Comprehensive searches were performed in international electronic databases including Scopus, PubMed, and Web of Science, as well as Iranian databases such as Iranmedex, from inception to February 1, 2024, utilizing keywords derived from Medical Subject Headings such as "acupressure", "anxiety", and "chemotherapy". The methodological quality of randomized controlled trials (RCTs) and quasi-experimental studies was assessed using the Joanna Briggs Institute's critical appraisal checklist. A total of five studies, encompassing 401 cancer patients undergoing chemotherapy, were included in the review. Among these patients, 83.26% were female, with 54.36% assigned to the intervention group. The mean age of participants was 51.01 (SD=8.52) years. Of the included studies, three were RCTs and two were quasi-experimental studies. The average study duration and follow-up period were approximately 31 weeks and 35 days, respectively. Moreover, the average duration of the intervention was 18 minutes. Across all studies, acupressure interventions demonstrated efficacy in reducing anxiety levels among cancer patients undergoing chemotherapy. The findings suggest that healthcare professionals, particularly nurses, can effectively utilize acupressure techniques to alleviate anxiety in this patient population. It is recommended that healthcare managers and policymakers facilitate the integration of acupressure interventions into hospital settings, thereby enhancing the provision of care and support for cancer patients undergoing chemotherapy.